Static and dynamic evaluation of Silicon-On-Insulator-based scanning micromirrors. (6th May 2008) - You, Jianliang; Bhaskar, Avinash K.; Packirisamy, Muthukumaran; Bhat, Rama B.
Microfabricated Silicon-On-Insulator (SOI) optical micromirrors are often used in switching applications due to their high reflectivity and low residual stress. In the present study, an industrial bulk micromachining technology based on SOI wafer called the MicraGEM SOI technique is used to fabricate the micromirror. Further, analytical studies were carried out for the static and dynamic characteristics, and are validated using experimental results. A test set-up comprising a laser source and Laser Doppler Vibrometer (LDV) was used for dynamic testing. The microfabrication and test method proposed are simple and can be used to study optical micromirrors of any size.